Farinha de penas em dietas para Tilápia do Nilo - Finkler, Joana Karin (2013)
Current analysis evaluates the inclusion effect of feather meal in diets with and without aminoacids supplementation on the performance, centesimal composition, hematological parameters and feeding costs of Nile tilapia fingerlings, Oreochromis niloticus. One thousand and four hundred Nile tilapia fingerlings, initial average weight 4.98±0.08 g, distributed in 28 small cages of 1m³, with 50 fish each, were used. Three levels (8, 16 and 24%) of hydrolyzed feather meal (FM) inclusion and two groups, one with and the other without synthetic aminoacids supplementation (AAs), were evaluated during 65 days. Control treatment with neither feather meal nor aminoacids supplementation was also employed, totalizing seven treatments and four replications. Productive performance analysis including total length (TL), weight gain (WG), apparent food conversion (AFC), survival (SU), condition factor (CF) and protein efficiency rate (PER) was performed at the end of the experiment, coupled to body parameters such as visceral fat index (VFI) and hepatosomatic index (HIS). Blood samples were collected for erythrocytes counting and determination of hemoglobin, hematocrit, average corpuscular volume (ACV) and average corpuscular hemoglobin concentration (ACHC). The entire fish was used for the analysis of centesimal composition, namely, moisture (MO), protein (P), ether extract (EE) and mineral matter (MM)). Diet costs per kilo of WG were also assessed. Treatments did not influence (p>0.05) SU, HIS, CF, MO and MM and best results for FM and WG were those of treatments with 8% FM with or without AAs supplementation. AFC was higher and PER lower in treatments with 24% FM without supplementation. P rate was lower in treatment with inclusion of 24% FM without supplementation when compared to control, whereas EE had higher levels of inclusion when compared to control. Hematologic parameters were kept within the species´s normal variation level. Treatment with 8% FM with supplementation presented lower feeding costs. Results show that feather meal may be used in diets for Nile tilapia up to 8% inclusion, with or without supplementation of AAs, without any liability in performance, chemical composition and higidity. In fact, supplementation at the above inclusion level with AAs is economically more viable